NITRATE CONTENT AS EXPORT CONSTRAIN OF INDONESIAN VEGETABLES TO EUROPE - Ketut Anom Wijaya (UPT Penerbitan Universitas Jember, 2012)
Vegetable quality is determined by the physical properties, chemistry, color, and taste. Since increased public awareness of health, their demand on food quality has alsoincreased. Chemical properties of vegetables include: level of nitrate, pesticide residue andheavy metal content. The purpose of this paper is to provide information to Indonesianvegetables stakeholder, the European markets impose strict conditions on levels of nitratevegetables. The method used is the study of literature from a variety of credible sources. Inthe human’s stomach is reduced nitrate to nitrite, then nitrite reacts with amines to formnitrosamine compound. Nitrosamine is known as a very potential carcinogenic compound,with risk of 90%. Statistically, 72.4% of daily nitrate intake originated from vegetables,equal to 35.7 mg/day. Besides forms nitrosamine, nitrite couse methemoglobinamie (babyblue syndrome). Nitrate is very serious threat to human health, so that the WHO limit the maximum daily nitrate intake do not exceed 220 mg (Scharpf and Wehrmann, 1991). To protect their citizen against nitrate hazard, European government are agreed to limit themaximum nitrate content in vegetables. Each species of vegetable and Country has differentnitrate limit. Indonesian’s vegetable contain high nitrate level and difficult to reducebecause there is no technology have been developed to quantify N supply to achieve lownitrate content. Growers in developed countries (Europe, USA, Japan, and Canada) applyN-mineral Metode to maintain nitrogen supply and nitrate content. Wijaya (2012) haveanalyzed 5 species of vegetables (spinach, pachoy, cabage, lettuce and chinakol) resfectivlycontain 6.427, 3.915, 1.847, 1.553, and 704 mg/kg FS). Acording to these nitrate contentand nitrate limiting role of European Countries, very hard for Indonesia to exportIndonesian vegetables to Europe.